Influence of metal‐organic vapor phase epitaxy parameters and Si(111) substrate type on the properties of AlGaN/GaN HEMTs with thin simple buffer. Issue 4 (16th November 2016) - Frayssinet, Eric; Leclaire, Paul; Mohdad, Jad; Latrach, Soumaya; Chenot, Sébastien; Nemoz, Maud; Damilano, Benjamin; Cordier, Yvon
Abstract : The present work is dedicated to the study of the influence of metal‐organic vapor phase epitaxy (MOVPE) growth conditions on the properties of AlGaN/GaN high electron mobility transistor (HEMT) heterostructures with thin simple buffer layers on Si(111). In a first series of samples grown on high resistivity silicon, the conditions were varied within the GaN buffer layer while kept unchanged for the AlN nucleation layer and HEMT barrier and cap layers. XRD and AFM revealed some differences in epilayers structural quality especially in case of excessive growth pressure or V/III ratio. Capacitance–voltage (CV) measurements revealed differences in the pinch‐off regime of the two‐dimensional electron gas (2DEG) located at the AlN/GaN interface. Except in one case, the buffer leakage current between isolated devices correlates with the pinch‐off behavior. The majority of these structures exhibited sheet carrier densities of 1 × 10 13  cm −2 and electron mobility between 1100 and 1400 cm 2  V  −1  s −1 depending on the GaN channel growth conditions. The output and transfer characteristics (maximum drain currents and leakage currents) of the transistors are in agreement with the previous electrical characterizations. Thanks to the combination of structural and electrical characterizations we are then able to determine the optimized growth conditions for such HEMT structures. Compared with high resistivity silicon, we obtained better structural and electrical quality on conductive substrates. A 2DEG with an electron mobility of 1700 cm 2  V −1  s −1 has been achieved within a structure with a 0.5 μm thick buffer producing an off‐state breakdown voltage of 117 V. This reveals the crucial role of the substrate surface properties on the resulting quality of the heterostructures.